KARAKTERISASI KUALITAS BUAH EMPAT GENOTIP PEPAYA (Carica papaya L.) KOLEKSI BALAI PENELITIAN TANAMAN BUAH TROPIKA - Dewi Fatria; Noflindawati Noflindawati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
The research was conducted at Post Harvest Laboratory of Indonesian Tropical Fruit Research Institute (ITFRI) from March to May 2010. The design used was a randomized complete block design with 4 replicates. Papaya genotypes tested were BT-01, BT-02, BT-03, and BT-04. The results showed that papaya genotypes of BT-01, BT-02, BT-03, and BT-04 were not significantly different each other on physical fruit characters i.e. fruit length, fruit width, fruit weight, and stem length. However, the thinnest fruit flesh was found at BT-3 genotype and the thicknest flesh was at BT-2 genotype. The lowest fruit cavity was found at genotype BT-1 and the highest was at the BT-2. The lowest hardness of fruit skin and flesh was found at genotype BT-4 and the highest hardness of skin was at BT-3, while the highest hardness of flesh was at BT-1 and BT-2. Chemical quality of total dissolved solid, vitamin C, acid content, and water content was not significantly different among the four genotypes BT-1, BT-2, BT-3, and BT 4.